1987
DOI: 10.1093/imanum/7.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Finite-Difference Schemes for Elliptic Equations with Variable Coefficients

Abstract: Abstract. First boundary value problem for elliptic equation with youngest coefficient containing Dirac distribution concentrated on a smooth curve is considered. For this problem a finite difference scheme on a special quasiregular grid is constructed. The finite difference scheme converges in discrete W 1 2 norm with the rate O(h 3/2 ). Convergence rate is compatible with the smoothness of input data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…Schemes for less regular coefficients (on uniform grids) are also known [11,12,15,20,28], which are based on earlier work by Samarskij [27]. We also impose the general assumption that the homogeneous problem (2.1), i.e., with g = 0 and = 0, has only the solution u = 0.…”
Section: A Fully Discrete Galerkin Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Schemes for less regular coefficients (on uniform grids) are also known [11,12,15,20,28], which are based on earlier work by Samarskij [27]. We also impose the general assumption that the homogeneous problem (2.1), i.e., with g = 0 and = 0, has only the solution u = 0.…”
Section: A Fully Discrete Galerkin Approximationmentioning
confidence: 99%
“…So it appears natural, as our results show, that the H 1 error estimates obtained for the FDM are closely related to supercloseness of the FEM. But the literature gives the impression that there exist the two separated communities of the FEM and FDM people (see [12,13,15,28] and the overview in [11] for the latter) and the relation of those results has not been considered in that respect.…”
mentioning
confidence: 99%
“…Let us consider the sum where the mesh function v is extended outsideω by (9). Using the periodicity and orthogonality of sines, from (9) follows…”
Section: Stability Of Fdsmentioning
confidence: 99%
“…The term η ij can be estimated in the same manner as in the case of the Dirichlet boundary-value problem (see [9], [7]):…”
Section: Proof Under the Previous Assumptions Ifmentioning
confidence: 99%
“…It is shown that the approximations converge at rate ∆x λ−2 in the energy norm (a discrete version of the H 1 -norm). In [10], this result is extended to coefficients a ij (x) ∈ W λ−1,2 (D), a(x) ∈ W λ−2,2 (D). Another related work is the article [13] by V. Jovanović and C. Rohde where they establish error estimates for finite volume approximations of linear hyperbolic systems in multiple space dimensions for initial data with low regularity, however under the assumption that the coefficients are smooth.…”
Section: Introductionmentioning
confidence: 99%